Free vibration analysis of functionally graded graphene platelet-reinforced metal foam doubly curved panel - Zhang, Li-Li; Zhao, Li-Cai; Lang, Song-Jun; Asemi, Kamran (Frontiers in Materials, 2024)
In this research, free vibrations characteristics of functionally graded metal foam doubly curved panel reinforced with graphene platelet and with porosities have been surveyed. Halpin Tsai approach is utilized for extracting the effective Young modulus of porous metal foam nanocomposite and also the the effective density of nanocomposite porous doubly curved shell panel is estimated by using extended rule of mixture. FSDT hypothesis is utilized for determining the displacement field and Finite element and Hamilton principle are utilized for deriving the mass and stiffness matrices of the structure. Finally, the influences of sevaral variables such as porosity distribution, porosity coefficient, GPL dispersion pattern, weight fraction of Nano fillers and span angles on the free vibrations characteristics of doubly curved shell panel with FG porosities and reinforced by graphene platelet have been reported in detail.